MENINGKATKAN KESEJAHTERAAN PEREKONOMIAN INDONESIA BERBASIS ISLAMIC ENTREPRENUERSHIP - Budiyono Santoso; Matnin Matnin; Maskuri Bakri (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The purpose of this research is to improve the welfare of the Indonesian people. Of course the solution is not only to prepare strong macroeconomic fundamentals, an increased investment climate, but also the need for programs that encourage many entrepreneurial entrepreneurs in the real and non-formal sectors. This research also reveals about welfare in an Islamic perspective which is characterized by the achievement of welfare in accordance with maqaashid al sharia, as well as revealing about the characteristics of Muslim interpreneurship, namely having a strong vision, being creative, oriented to customer satisfaction, daring to take risks and having a social spirit. The writing method used is a qualitative approach method. While the method used is to analyze the concept and look for relevant reference sources, such as using journals, books, theses, articles, magazines and so on. The analysis used is in the form of a descriptive analysis that provides an explanation of the analysis and synchronizes it with the existing literature. The original of this research is that the welfare of the Indonesian economy requires the role of entrepreneurs who are able to manage natural resources into products with high added value. In order to produce the entrepreneurs above, Muslims need to learn the values ​​of entrepreneurship that have been taught by the Qur'an and Al-Hadith, namely the values ​​contained in Surah Quraish.